2016
DOI: 10.1007/s10495-016-1267-9
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroceramide-desaturase-1-mediated caspase 9 activation through ceramide plays a pivotal role in palmitic acid-induced HepG2 cell apoptosis

Abstract: In this study, results showed that the inhibition of PA-induced HepG2 cell growth takes place in a time- and concentration-dependent manner, that activation of caspase 9 is necessary for PA-induced HepG2 cell apoptosis, that dihydroceramide desaturase 1 (DES1) plays a key role in PA-mediated caspase 9 and caspase 3 activation, and that palmitoleic acid (POA), an omega-7 monounsaturated fatty acid, reverses PA-induced apoptosis through DES1 → Ceramide → Caspase 9 → Caspase 3 signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…Moreover, in the BCL 2 family, BAX has a proapoptotic effect (Chen et al 2010;He et al 2018;Mu et al 2001). In the present study, the Caspase 3 activation (Zhu et al 2016) and BAX expression (He et al 2018) was upregulated after PA treatment, as previously shown in other studies. Based on these results, we concluded that PA can regulate Caspase 3 activation and BAX expression to affect cell apoptosis in Saos-2 cells.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in the BCL 2 family, BAX has a proapoptotic effect (Chen et al 2010;He et al 2018;Mu et al 2001). In the present study, the Caspase 3 activation (Zhu et al 2016) and BAX expression (He et al 2018) was upregulated after PA treatment, as previously shown in other studies. Based on these results, we concluded that PA can regulate Caspase 3 activation and BAX expression to affect cell apoptosis in Saos-2 cells.…”
Section: Discussionsupporting
confidence: 90%
“…Both are precursors of apoptosis [ 42 44 ], possibly due to the homeostatic disturbance related to the low pH (3.5 to 4.5) that is characteristic of this vaginosis [ 5 ]. Additionally, the increase in the levels of palmitoleic acid and 1-oleoyl-cyclic phosphatidic acid in the CV group was consistent with the role of these acids on injured epithelial tissues, already described this relation in hepatic cells [ 45 ]. Our results showed the presence of these potential lipids biomarkers in CV group which can be inferred the possible relation of injured caused on the vaginal epithelium visualized on the Gram stain.…”
Section: Discussionsupporting
confidence: 85%
“…It is well-known that SGMS2 is a key enzyme in the hemeostasis of Cer, which is tightly associated with cell apoptosis 5,11 . Many studies have revealed that ceramide plays a pivotal role in cell apoptosis via the P-AKT → caspase-3 → PARP signalling pathway in several types of diseases, including renal cell carcinoma 12 , hepatocellular carcinoma 13,14 and retinopathy 15 . To determine the mechanism underlying the SGMS2-induced increase in cell proliferation, we investigated the expression of Cer and activation of the Cer-associated apoptosis pathway.…”
Section: Resultsmentioning
confidence: 99%